2011
DOI: 10.1111/j.1600-0609.2011.01627.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic transplantation using haploidentical donor vs. unrelated cord blood donor in pediatric patients: a single-center retrospective study

Abstract: We retrospectively analyzed outcomes in 67 children with acute leukemia who received hematopoietic stem cell transplantation from alternative allogeneic donors: 29 received a haploidentical family donor and 38, an unrelated cord blood donor. All transplantations were performed from 1996 through 2010 in our center. Neutrophil and platelet engraftment were significantly delayed after cord blood transplantation. The median times to neutrophil and platelet recovery were 13 d (7-34) and 11 d (5-70) after haploident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…24,26,28 Our data suggest that both approaches provide similar transplant outcomes, a conclusion also reached by other groups. 19 Leung et al 20 also demonstrated that, for children with acute leukemia, modern haploidentical HCT provides similar outcomes to both matched sibling and unrelated donor HCTs. Their results, in combination with ours and others, 19,21 suggest that haploidentical HCT should be more widely utilized for patients with otherwise incurable diseases.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…24,26,28 Our data suggest that both approaches provide similar transplant outcomes, a conclusion also reached by other groups. 19 Leung et al 20 also demonstrated that, for children with acute leukemia, modern haploidentical HCT provides similar outcomes to both matched sibling and unrelated donor HCTs. Their results, in combination with ours and others, 19,21 suggest that haploidentical HCT should be more widely utilized for patients with otherwise incurable diseases.…”
Section: Discussionmentioning
confidence: 98%
“…19 Leung et al 20 also demonstrated that, for children with acute leukemia, modern haploidentical HCT provides similar outcomes to both matched sibling and unrelated donor HCTs. Their results, in combination with ours and others, 19,21 suggest that haploidentical HCT should be more widely utilized for patients with otherwise incurable diseases. One situation where haploidentical transplant may be preferable over cord blood is when attempting posttransplant immune manipulation via DLI to reduce relapse 29 or treat opportunistic infections.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[10][11][12][13][14] Although all of our patients received GVHD prophylaxis with calcineurin inhibitors and mycophenolate mofetil, the incidences of severe acute and chronic GVHD were acceptable for our partial depletion of T cells.…”
Section: Discussionmentioning
confidence: 95%
“…There have been several reports on HHCT using CD3-depleted grafts in pediatric patients. 2,[10][11][12][13][14] The Tübingen group reported their experience with CD3/19-depleted HHCT using reduced-intensity conditioning in 38 pediatric patients. 2 The authors reported a primary engraftment rate of 83%, with GR occurring in 17% of patients.…”
Section: Discussionmentioning
confidence: 99%